Body image disturbance and its associations with physical activity level in body builder practitioners in the city of Cacoal-RO - Santos, Ana Paula Rid dos (2012)
The standard of beauty imposed nowadays is more frequent to the distortion dissatisfaction with body image, which can lead to the development of behaviors for weight control. This study has as aim to relate the body image disturbance and its associations with physical activity level and BMI in body builder practitioners in the city of Cacoal-RO. It was evaluated 117 individuals, among 18 to 35 years old, being 40 individuals of the male kind and 77 individuals of the female kind. It was applied the international physical activity questionnaire (IPAQ); the questionnaire about body image (BSQ); and it was checked the weight and the stature to the calculation for the body mass index (BMI). The results were analyzed through the BIOSTATIC program, beside the analysis of correlation of Pearson. The study pointed that there was a prevalence of normality in the perception of the body image among men and women, but the female genre presented a trend to have a lightdistortion of its actual and ideal body image, not being observed in the case of the male kind evaluated, what can lead, in several problems like, for example, risk of developing eating disorders.